Análise comparativa do perfil cardiorrespiratório pós COVID-19 em mulheres portadoras de câncer de mama - Brasil, Ani Paula Scramocin (2024)
Breast cancer is a complex disease associated with the occurrence of immunosuppression due to several factors. This makes these patients at greater risk of developing infectious diseases such as COVID-19 in its most severe form, and may present sequelae even after the infection period. The objective of the present study was to perform a comparative analysis of the cardiorespiratory profile after COVID-19 in women with breast cancer treated at SUS. This is a mixed case-control study, carried out from January 2020 to June 2024 at the Francisco Beltrão Cancer Hospital - PR. Four groups of 14 participants each were analyzed, matched by age, with and without a history of COVID-19, with or without breast cancer. All participants underwent respiratory muscle strength testing, cardiorespiratory functional capacity testing, and assessment of the presence of dyspnea. For women with breast cancer, information regarding the clinical-pathological profile of the disease was also collected. The results were analyzed using GraphPad Prism version 9.0. A significant reduction in respiratory muscle strength was identified in participants who had COVID-19 and had breast cancer. In contrast, these women covered significantly greater distances in the walking test. Dyspnea, regardless of the presence of cancer, was the predominant symptom reported in women with a history of COVID-19. These findings demonstrate that SARS-CoV2 infection significantly impacts the reduction in respiratory muscle strength and the presence of dyspnea, without reducing cardiorespiratory functional capacity.